The Autophagy-Related Gene Aolatg4 Regulates Hyphal Growth, Sporulation, Autophagosome Formation, and Pathogenicity in Arthrobotrys oligospora - Zhou, Duanxu; Xie, Meihua; Bai, Na; Yang, Le; Zhang, Ke-Qin; Yang, Jinkui (Frontiers in Microbiology, 2020)
Autophagy plays an important role in cell growth and development. The autophagy-related gene atg4 encodes a cysteine protease, which can cleave the carboxyl terminus of Atg8, thus plays a role in autophagosome formation in yeast and filamentous fungi. Arthrobotrys oligospora is well known for producing special trapping-devices (traps) and capturing nematodes. In this study, two ΔAolatg4 mutants were generated using targeted gene replacement and were used to investigate the biological functions of autophagy in A. oligospora. Autophagic process was observed using the AoAtg8-GFP fusion protein. The mutants showed a defective in hyphal growth and sporulation, and were sensitive to chemical stressors, including menadione and Congo red. The spore yield of the ΔAolatg4 mutants was decreased by 88.5% compared to the WT, and the transcript levels of six sporulation-related genes, such as abaA, fluG, brlA, and wetA, were significantly downregulated during the conidiation stage. Deletion of Aolatg4 also affected the cell nuclei and mycelial septal development in A. oligospora. Importantly, autophagosome formation and the autophagic process were impaired in the ΔAolatg4 mutant. Moreover, the ΔAolatg4 mutant lost its ability to form mature traps. Our results provide novel insights into the roles of autophagy in A. oligospora.